2009
DOI: 10.2478/s11686-009-0041-3
|View full text |Cite
|
Sign up to set email alerts
|

Opecoelids (Platyhelminthes, Digenea) from the fork-tailed threadfin bream Nemipterus furcosus (Valenciennes, 1830) (Perciformes, Nemipteridae), with preliminary keys to the problematic genera Macvicaria Gibson et Bray, 1982 and Neolebouria Gibson, 1976

Abstract: The opecoelid species Macvicaria jagannathi (Gupta et Singh, 1985) Bijukumar, 1997 (new syn. Plagioporus deeghaensis Gupta et Gupta, 1988) and Neolebouria lineatus Aken’Ova et Cribb, 2001 are redescribed from Nemipterus furcosus, from the waters off New Caledonia. Provisional keys to the genera Macvicaria Gibson et Bray, 1982 and Neolebouria Gibson, 1976 are presented. The following new combinations are made: Macvicaria yamagutii (Gupta et Ahmad, 1977), M. puriensis (Gupta et Govind, 1984) and M. chilkai (Gupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…n. is chosen as the type species because it is coupled with molecular data. Bray and Justine (2009a) suggested that the deepwater snappers (primarily Pristipomoides) likely hosted a monophyletic clade of opecoelids that share similar morphological features and life-histories. We agree with them and propose the combinations Bentholebouria blatta (Bray et Justine, 2009) comb.…”
Section: Resultsmentioning
confidence: 99%
“…n. is chosen as the type species because it is coupled with molecular data. Bray and Justine (2009a) suggested that the deepwater snappers (primarily Pristipomoides) likely hosted a monophyletic clade of opecoelids that share similar morphological features and life-histories. We agree with them and propose the combinations Bentholebouria blatta (Bray et Justine, 2009) comb.…”
Section: Resultsmentioning
confidence: 99%
“…We are defining the forebody and hindbody as the regions anterior to and posterior to the ventral sucker, respectively, although some workers define these regions differently. The use of the key to the species of Neolebouria in Bray & Justine (2009) indicates that N. blatta n. sp. is closest to N. georgenascimentoi Bray, 2002 from the rollizo sandperch Pinguipes chilensis Valenciennes, the tilefish Prolatilus jugularis (Valenciennes) and the namorado sandperch Pseudopercis numida Miranda Ribeiro (all Pinguipedidae) off Chile and Brazil (Bray, 2002;Luque, et al, 2008;González & Oliva, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the few opecoelids known to utilise fishes as its second intermediate host [83]. Of the other species, Neolebouria blatta is reported only from New Caledonia, N. lineatus only from southern Western Australia, and Macvicaria jagannathi from the Bay of Bengal [84-88]. …”
Section: Discussionmentioning
confidence: 99%
“…New, unpublished records indicated by [0]; other records: [6,24,25,45,47,58,59,71,78,79,81,87,88,107,155-166]. …”
Section: Appendix 1 Host-parasite Listmentioning
confidence: 99%